BLACK SPOT STUDY - Prof. Y. B. Survase; Dr.M. G. Dheshmukh; Aniket Burange; Dnyaneshwar Raut; Siddheshwar Dudhani; Suraj Bhosale; Sumit Pawar (International Journal of Innovations in Engineering Research and Technology, 2022)
India is one of the fastest developing nations in the world, thus resulting in more buying capacity for its citizens. There is explosion of vehicles on Indian highways which has surged by more than 400 percent from 2001 to 2013 i.e., in 12 years comparing it to National highways which merely has grown by 133 percent, thus resulting in congestion and increase of accident rates in India. Black spots are being declared throughout the country in countries own about 52 percent of the world’s vehicle but they account for more than 88 percent of the world’s road traffic fatalities. By this rate of growth, the fatal accidents are going to be the 5th largest cause of accident in the world by 2020. Pedestrians, Cyclist and Motorbikes together form around 57 percent of death rates happening on the roads of the world, out of which persons in the age group of 15 to 44 years account for more than 60 percent of world’s total fatal accident rates. Literature Review has been carried out showing the scenario of accidents happening on different highways of India along with its causes and solutions.